2020
DOI: 10.1111/cobi.13622
|View full text |Cite
|
Sign up to set email alerts
|

Determining the role of eudaimonic values in conservation behavior

Abstract: Values are the fundamental reasons why people engage in conservation behaviors. Recent research has called for a more refined approach to studying values in a way that accounts for the concept of eudaimonia. However, the empirical properties for a eudaimonic value scale have not been tested given that previous investigations have remained at the theoretical level. Drawing from an on-site survey of visitors to Denali National Park and Preserve, Alaska, we used a latent profile analysis to better understand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 69 publications
(172 reference statements)
0
10
0
Order By: Relevance
“…These authors showed that PEB spanned the dimensions of conservation lifestyles, environmental citizenship, social environmentalism, and land stewardship behaviors, while also indicating that careful attention should be paid to the structure of PEB as a first- or second-order factor model. Given the importance of socialization in both PEB and human-place bonding ( Kyle and Chick, 2007 ), social environmentalism has also been identified as an important aspect of place attachment, alongside actions that are relevant to public and private domains ( Landon et al, 2018 ; van Riper et al, 2019 ; Winkler-Schor et al, 2020 ; Golebie et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These authors showed that PEB spanned the dimensions of conservation lifestyles, environmental citizenship, social environmentalism, and land stewardship behaviors, while also indicating that careful attention should be paid to the structure of PEB as a first- or second-order factor model. Given the importance of socialization in both PEB and human-place bonding ( Kyle and Chick, 2007 ), social environmentalism has also been identified as an important aspect of place attachment, alongside actions that are relevant to public and private domains ( Landon et al, 2018 ; van Riper et al, 2019 ; Winkler-Schor et al, 2020 ; Golebie et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Positive impacts of stewardship on entity integrity benefit people because they maintain nature's potential to provide positive contributions (Brauman et al., 2020), but these benefits are often intangible to the stewards themselves. Importantly, stewardship can have direct positive impacts on the quality of life of a steward via eudaimonia—satisfaction derived from acting righteously (Pritchard et al., 2020; Winkler‐Schor et al., 2020). Thus, relational norms that make stewardship feel rewarding can motivate actions with positive impacts on entities of nature (Chan et al., 2016; Richardson, Passmore, et al., 2020).…”
Section: The Iren Typologymentioning
confidence: 99%
“…A person's values and judgements will be influenced by a multitude of factors, including age, gender, race, class, wealth and other elements of their social, cultural, political and geographic context (e.g. Winkler-Schor et al, 2020). These in turn may determine research interests and outputs, including motivations for engaging in conservation messaging (Neely & Nguse, 2015).…”
Section: Be Reflexivementioning
confidence: 99%